2012
DOI: 10.1051/0004-6361/201118111
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-stellar objects in the ALHAMBRA survey

Abstract: Context. Even the spectroscopic capabilities of today's ground and space-based observatories can not keep up with the enormous flow of detections (>10 5 deg −2 ) unveiled in modern cosmological surveys as: i) would be required enormous telescope time to perform the spectroscopic follow-ups and ii) spectra remain unattainable for the fainter detected population. In the past decade, the typical accuracy of photometric redshift (photo-z) determination has drastically improved. Nowdays, it has become a perfect com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 72 publications
(95 reference statements)
0
28
1
Order By: Relevance
“…Unfortunately, the i-dropouts and broad-band colours of a z ∼ 5-6 QSO can look very similar to those of evolved/passive galaxies at z ∼ 1 or of local red giants and super-giants. Matute et al (2012) have shown that using the 23 bands of the ALHAMBRA photometric catalogue makes it possible to efficiently classify a high percentage (∼90%) of the z = [0, 3] BLAGN/QSO population and measure highly accurate photometric redshifts.…”
Section: High-z Qsos Candidatesmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, the i-dropouts and broad-band colours of a z ∼ 5-6 QSO can look very similar to those of evolved/passive galaxies at z ∼ 1 or of local red giants and super-giants. Matute et al (2012) have shown that using the 23 bands of the ALHAMBRA photometric catalogue makes it possible to efficiently classify a high percentage (∼90%) of the z = [0, 3] BLAGN/QSO population and measure highly accurate photometric redshifts.…”
Section: High-z Qsos Candidatesmentioning
confidence: 99%
“…We have applied the methodology described by Matute et al (2012) to the search for high-z (z > 5) QSOs using the ALHAMBRA photometric database. The candidates were selected over ≈1 deg 2 in the two ALHAMBRA fields (out of eight; ALH-2/DEEP2 and ALH-8/SDSS) observable from the Roque de los Muchachos observatory in La Palma during the 2011B semester according to the following criteria: i) located in the fully exposed areas of the images and in regions not contaminated by bright sources flux or artefacts (e.g.…”
Section: High-z Qsos Candidatesmentioning
confidence: 99%
See 2 more Smart Citations
“…We can note there is a large number of outliers in the sample. In Fig.2.7 we show the photometric redshift estimation for a sample of 170 quasars detected in the ALHAMBRA fields (Matute et al 2012). The analysis was performed with LePhare, using all of the 23 band filters and 50 templates (see more details in Chapter 5).…”
Section: Photometric Redshift Estimationmentioning
confidence: 99%